Analysis of efficacy of lung resections and pneumonectomies in patients with fibrous cavernous tuberculosis depending on disease activity - D. E. Omelchuk; D. V. Krasnov; Т. I. Petrenko; I. A. Bolshakova (Туберкулез и болезни лёгких)
The objective: to study the frequency of post-operative complications and outcomes of lung resections and pneumonectomies in patients with fibrous cavernous tuberculosis depending on the activity of tuberculous inflammation.Subjects and methods. 722 patients were enrolled into the study, they all underwent radical surgery for fibrous cavernous pulmonary tuberculosis in the Krasnoyarsk Regional TB Dispensary No. 1. In all cases, the diagnosis of fibrous cavernous tuberculosis was confirmed by pathomorphological tests after surgery. The severity of tuberculous inflammation was evaluated based on the following generally available indicators: massivity of bacterial excretion, erythrocyte sedimentation rate, x-ray changes over 2 months before the surgery. Depending on the activity of the disease, patients were divided into three groups: those with low activity (479 patients), medium activity (171 patients) and high activity (72 patients).Results. The outcome of resection surgery due to fibrous cavernous pulmonary tuberculosis performed in patients with low tuberculosis activity was more favorable compared to moderate and high exacerbation activity and especially pronounced exacerbation, as indicated by the achievement of a complete clinical effect in 92.7, 74.3, and 37.5%, respectively, and a more favorable course of the postoperative period. Thus, the frequency of severe postoperative complications made in 12.1, 26.3, and 55.6% of patients, respectively. This situation was also confirmed in operations of the same type (among patients with pneumonectomy and among patients with lung resection). The high activity of tuberculosis should be considered a relative contraindication to surgical resections.